Interventions for maintenance of surgically induced remission in Crohn’s disease: a network meta‐analysis - Iheozor‐Ejiofor, Zipporah (Cochrane Database Syst Rev, 2019)
BACKGROUND: Crohn's disease (CD) is a chronic disease of the gut. About 75% of people with CD undergo surgery at least once in their lifetime to induce remission. However, as there is no known cure for the disease, patients usually experience a recurrence even after surgery. Different interventions are routinely used in maintaining postsurgical remission. There is currently no consensus on which treatment is the most effective. OBJECTIVES: To assess the effects and harms of interventions for the maintenance of surgically induced remission in Crohn's disease and rank the treatments in order of effectiveness. SEARCH METHODS: We searched the Cochrane IBD Group Specialized Register, CENTRAL, MEDLINE, and Embase from inception to 15 January 2019. We also searched reference lists of relevant articles, abstracts from major gastroenterology meetings, ClinicalTrials.gov, and the WHO ICTRP. There was no restriction on language, date, or publication status. SELECTION CRITERIA: We considered for inclusion randomised controlled trials (RCTs) that compared different interventions used for maintaining surgically induced remission in people with CD who were in postsurgical remission. Participants had to have received maintenance treatment for at least three months. We excluded studies assessing enteral diet, diet manipulation, herbal medicine, and nutritional supplementation. DATA COLLECTION AND ANALYSIS: Two review authors independently selected relevant studies, extracted data, and assessed the risk of bias. Any disagreements were resolved by discussion or by arbitration of a third review author when necessary. We conducted a network meta‐analysis (NMA) using a Bayesian approach through Markov Chain Monte Carlo (MCMC) simulation. For the pairwise comparisons carried out in Review Manager 5, we calculated risk ratios (RR) with their corresponding 95% confidence intervals (95% CI). For the NMA, we presented hazard ratios (HR) with corresponding 95% credible intervals (95% CrI) and reported ranking probabilities for each intervention. For the NMA, we focused on three main outcomes: clinical relapse, endoscopic relapse, and withdrawals due to adverse events. Data were insufficient to assess time to relapse and histologic relapse. Adverse events and serious adverse events were not sufficiently or objectively reported to permit an NMA. We used CINeMA (Confidence in Network Meta‐Analysis) methods to evaluate our confidence in the findings within networks, and GRADE for entire networks. MAIN RESULTS: We included 35 RCTs (3249 participants) in the review. The average age of study participants ranged between 33.6 and 38.8 years. Risk of bias was high in 18 studies, low in four studies, and unclear in 13 studies. Of the 35 included RCTs, 26 studies (2581 participants; 9 interventions) were considered eligible for inclusion in the NMA. The interventions studied included 5‐aminosalicylic acid (5‐ASA), adalimumab, antibiotics, budesonide, infliximab, probiotics, purine analogues, sulfasalazine, and a combination of sulfasalazine and prednisolone. This resulted in 30 direct contrasts, which informed 102 mixed‐treatment contrasts. The evidence for the clinical relapse network (21 studies; 2245 participants) and endoscopic relapse (12 studies; 1128 participants) were of low certainty while the evidence for withdrawal due to adverse events (15 studies; 1498 participants) was of very low certainty. This assessment was due to high risk of bias in most of the studies, inconsistency, and imprecision across networks. We mainly judged individual contrasts as of low or very low certainty, except 5‐ASA versus placebo, the evidence for which was judged as of moderate certainty. We ranked the treatments based on effectiveness and the certainty of the evidence. For clinical relapse, the five most highly ranked treatments were adalimumab, infliximab, budesonide, 5‐ASA, and purine analogues. We found some evidence that adalimumab (HR 0.11, 95% Crl 0.02 to 0.33; low‐certainty evidence) and 5‐ASA may reduce the probability of clinical relapse compared to placebo (HR 0.69, 95% Crl 0.53 to 0.87; moderate‐certainty evidence). However, budesonide may not be effective in preventing clinical relapse (HR 0.66, 95% CrI 0.27 to 1.34; low‐certainty evidence). We are less confident about the effectiveness of infliximab (HR 0.36, 95% CrI 0.02 to 1.74; very low‐certainty evidence) and purine analogues (HR 0.75, 95% CrI 0.55 to 1.00; low‐certainty evidence). It was unclear whether the other interventions reduced the probability of a clinical relapse, as the certainty of the evidence was very low. Due to high risk of bias and limited data across the network, we are uncertain about the effectiveness of interventions for preventing endoscopic relapse. Whilst there might be some evidence of prevention of endoscopic relapse with adalimumab (HR 0.10, 95% CrI 0.01 to 0.32; low‐certainty evidence), no other intervention studied appeared to be effective. Due to high risk of bias and limited data across the network, we are uncertain about the effectiveness of interventions for preventing withdrawal due to adverse events. Withdrawal due to adverse events appeared to be least likely with sulfasalazine (HR 1.96, 95% Crl 0.00 to 8.90; very low‐certainty evidence) and most likely with antibiotics (HR 53.92, 95% Crl 0.43 to 259.80; very low‐certainty evidence). When considering the network as a whole, two adverse events leading to study withdrawal (i.e. pancreatitis and leukopenia) occurred in more than 1% of participants treated with an intervention. Pancreatitis occurred in 2.8% (11/399) of purine analogue participants compared to 0.17% (2/1210) of all other groups studied. Leukopenia occurred in 2.5% (10/399) of purine analogue participants compared to 0.08% (1/1210) of all other groups studied. AUTHORS' CONCLUSIONS: Due to low‐certainty evidence in the networks, we are unable to draw conclusions on which treatment is most effective for preventing clinical relapse and endoscopic relapse. Evidence on the safety of the interventions was inconclusive, however cases of pancreatitis and leukopenia from purine analogues were evident in the studies. Larger trials are needed to further understand the effect of the interventions on endoscopic relapse.